Competitive behaviour of benzimidazole resistant strains of Penicillium italicum in citrus - and BRIGITTE BRETSCHNELDER, B.A. ULLASA1, OM PRAKASH2, J.W. ECKERT (Indian Phytopathology, 2002)
To study the fitness of benzimidazole resistant strains of Penicillium italicum causing blue mould rot citrus fruit. The spores of benzimidazole sensitive strains were mixed with six different resistant strains at equal proportions to produce the disease in healthy lemon fruit. The competitive behaviour of resistant strains was studied by plating the spores from these artificially inoculated fruits for four generations. The tolerant strains were capable of surviving for extended periods along with sensitive strains even in the absence of selection pressure.